Pengembangan LKPD Berbasis STEM Untuk Meningkatkan Kemampuan Berpikir Kritis Siswa Pada Materi Fluida Dinamis - Ulina, Sri; Jubaidah, Jubaidah (Schrodinger Jurnal Ilmiah Mahasiswa Pendidikan Fisika, 2025)
Critical thinking skills are needed in the physics learning process, but students' critical thinking skills are still low due to a suboptimal learning approach. This article aims to develop and test the feasibility, practicality, and effectiveness of STEM-based Student Worksheets (LKPD) on dynamic fluid materials for students in class XI Science at SMA Negeri 1 Siantar. The type of research used is Research and Development (R&D) with the ADDIE development model. The results of the study show that STEM-based LKPD (1) is very feasible to use with an average assessment of 95.62% by material experts and an average assessment by design experts of 90%. (2) It has met the practical category reviewed from the student response questionnaire with an average of 84.67% in the small group test (7 students) and 87.63% in the large group test (30 students) with aspects of appearance, material presentation, STEM-based learning, and benefits. (3) Effective in improving students' critical thinking skills can be seen from the N-gain result of 0.68 with the medium category. This LKPD is designed to support active learning, oriented towards the development of 21st century skills such as critical thinking skills, creativity, collaboration, and communication. STEM approaches provide meaningful learning experiences and are able to relate learning concepts to everyday life. This article recommends the use of STEM-based LKPD as an alternative to improve students' critical thinking skills, especially on dynamic fluid materials.